The influence of sodium caseinate and β-casein concentrate on the physicochemical properties of casein micelles and the role of tea polyphenols in mediating these interactions. (15th January 2022) - van de Langerijt, Tessa M.; O'Mahony, James A.; Crowley, Shane V.
Abstract: The influence of different casein-based ingredients on the physicochemical properties of native casein micelles (CMs) was studied. Sodium caseinate (SCN) and β-casein concentrate (BCC) were mixed with milk protein concentrate (MPC) at different ratios (1:3, 1:1, 3:1), at a total protein concentration of 20 g/L. Tea polyphenols (TPP) were added to select samples to investigate their effect on CM-SCN and CM-BCC interactions. The results demonstrated decreasing structural integrity of CMs and increased levels of non-micellar casein, due to addition of SCN to MPC, which led to a decreasing turbidity over time and an increase in surface hydrophobicity. Addition of BCC to MPC resulted in an increase in turbidity over time and a decrease in surface hydrophobicity of the system. TEM images suggested that small micelles from BCC interacted with the surface of CMs. The SDS-PAGE results show that CMs in samples with TPP dissociated less, indicating that TPP stabilized the CMs structure. In conclusion, the two casein ingredients, SCN and BCC, have a different effect on the colloidal and physicochemical properties of CMs in MPC suspensions. This study will contribute to a greater understanding of the effect of mixed protein formulation strategies on the functional properties of beverage systems. Highlights: Sodium caseinate causes casein micelle dissociation. Beta-casein micelles interact with the surface of casein micelles. Ingredient type affects functionality of milk protein blends.